SIMILARITIES AND DIFFERENCES OF PERSONAL EXPRESSIONS IN ENGLISH AND UZBEK LANGUAGES - Scientific Supervisor: Feruza Muratkhojayeva; Kamolaxon Israiljan qizi Ashrabiyeva (Modern American Journals, 2025)
This article explores the similarities and differences of personal expressions in English and Uzbek languages. Personal expressions are linguistic units that convey the speaker’s identity, emotions, attitudes, and social position. The study examines how both languages reflect individuality and social relations through specific lexical, grammatical, and stylistic means. The research highlights that while English often uses pronouns, possessive forms, and stylistic markers to indicate the speaker’s personal stance, Uzbek relies on affixes, verb forms, and context-dependent expressions. Moreover, cultural and social factors significantly influence the use of personal expressions in both languages. The findings provide insights into cross-linguistic communication, translation studies, and language teaching, emphasizing the importance of understanding both structural and pragmatic aspects of personal expressions.
Keywords: Personal expressions, English language, Uzbek language, linguistic identity, cross-cultural communication, pragmatics, stylistics, lexical features, grammatical structures.